2019
DOI: 10.1111/cen.13933
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and metabolic effects of carbohydrate restriction in children with Prader‐Willi syndrome

Abstract: Objective: Macronutrient regulation of hyperphagia and adiposity in Prader-Willi syndrome (PWS) is poorly understood. We compared fasting and postprandial concentrations of hormones and metabolites in eight PWS children (age 9-18 years) fed, in random order, low carbohydrate, high-fat (LC, 15% carb; 65% fat; 20% protein) and low-fat, high carbohydrate (LF, 65% carb, 15% fat, 20% protein) diets matched for calories and protein.Methods: Participants were randomized to consume either the LC or LF diet during a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Meals high in carbohydrates (≥65% of total energy intake) are generally more potent than meals high in fat in suppressing ghrelin concentrations. [11][12][13][14] In a recent study, 15 we compared the effects of low-fat, high-carbohydrate (LF-HC) and low carbohydrate, high-fat (LC-HF) intake in children with PWS, and we found that the LC-HF diet lowered post-prandial insulin concentration, increased fasting and post-prandial glucagon-like peptide 1 (GLP-1) concentrations and increased fatty acid oxidation relative to the LF-HC diet. However, the effect of dietary protein on AG and DAG has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Meals high in carbohydrates (≥65% of total energy intake) are generally more potent than meals high in fat in suppressing ghrelin concentrations. [11][12][13][14] In a recent study, 15 we compared the effects of low-fat, high-carbohydrate (LF-HC) and low carbohydrate, high-fat (LC-HF) intake in children with PWS, and we found that the LC-HF diet lowered post-prandial insulin concentration, increased fasting and post-prandial glucagon-like peptide 1 (GLP-1) concentrations and increased fatty acid oxidation relative to the LF-HC diet. However, the effect of dietary protein on AG and DAG has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Due to lower fat oxidation, extra dietary carbohydrates can potentially lead to excess fat deposition in patients with PWS. Individuals with PWS were also found to have a preference for simple carbohydrates . Although limited, evidence suggests excessive carbohydrate intake, particularly simple carbohydrates, may contribute to weight gain before the onset of hyperphagia in children with PWS …”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Irizarry et al examined the impact of carbohydrate restriction on hyperphagia and adiposity in children with PWS . Children with PWS (n = 8, age 9‐18 years) were randomly assigned to either the low carbohydrate, high‐fat (LC, 15% carb; 65% fat; 20% protein) diet or the low‐fat, high carbohydrate (LF, 65% carb, 15% fat, 20% protein) diet during a first hospital admission and the second diet during a subsequent admission.…”
Section: Resultsmentioning
confidence: 99%
“…22 Because of these issues, some groups have studied the effects of a carbohydrate-restricted diet for weight control in adolescents with PWS (15% carbohydrates, 65% fat, and 20% protein). 23 This diet, while effective, at least in the short term, for improved glycemic and weight control, is associated with deficiencies in vitamin D, calcium, and fiber. Elevations in C-reactive protein, as well as liver function tests (ALT, AST), have been shown in individuals with PWS following a low-carbohydrate diet.…”
mentioning
confidence: 99%
“…Elevations in C-reactive protein, as well as liver function tests (ALT, AST), have been shown in individuals with PWS following a low-carbohydrate diet. 23 Additionally, a low-carbohydrate diet can affect the gut microbiome, including bacteria taxa, richness and diversity. 24 Although a few studies have shown potential beneficial effects of a low-carbohydrate diet on the gut microbiome, most studies have reported that a lowcarbohydrate diet has more significant negative effects on the gut microbiome, including lowered species diversity and increased pro-inflammatory bacteria.…”
mentioning
confidence: 99%